(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Gujjar community in Anantnag District of Kashmir Valley are facing a variety of difficulties and are not aware of the impacts of Modernization. They all are dominated by their traditional customs and bonds. They are internally different from other Gujjars as major population among them gave response to Interview Schedule. They want to achieve modern impact to change their lives and society in all sectors like Lifestyle, Education, Health, Communication and Transportation, Economy etc. Modernization has affected as well as changed the lifestyle of the Gujjar tribal people of the district in a positive direction. The progress of modernisation has improved their lifestyle and their thinking and they have got a lot of change in their social, economical and political aspects. The government policies like MGNREGS, NRLM, ITDP, PMGSY, S.S.A, Mobile Schools and other schemes has influence the spread of modernization among Gujjars. The technological improvement is also one of the most important causes of the improvement of the Gujjars. There are a lot of change in the method of agriculture, transport system and communication. Especially among the new generation of the telecommunication system (telephone, mobile, and internet) has been widely spread. It helps them to overcome from the conservative. The society has been modified.